Slaves and slavery in ancient Greek comic drama - Akrigg, Ben; Tordoff, Rob (Cambridge University Press, 2013)
How did audiences of ancient Greek comedy react to the spectacle of masters and slaves? If they were expected to laugh at a slave threatened with a beating by his master at one moment but laugh with him when they bantered familiarly at the next, what does this tell us about ancient Greek slavery? This volume presents ten essays by leading specialists in ancient Greek literature, culture and history, exploring the changing roles and representations of slaves in comic drama from Aristophanes at the height of the Athenian Empire to the New Comedy of Menander and the Hellenistic World. The contributors focus variously on individual comic dramas or on particular historical periods, analysing a wide range of textual, material-culture and comparative data for the practices of slavery and their representation on the ancient Greek comic stage.